Perbandingan Hukum Hak Cipta Fotografi Tanpa Izin Pencipta di Indonesia dan Amerika - Rita Kusmayanti (Fakultas Hukum, Universitas Internasional Batam, 2018)
This research try to find out how to protect the law for the copyright owner of photography based on Indonesian National Law and America and how to solve effort if dispute happen. The type of research used in this study is normative research. A normative study undertaken or demonstrated only on written rules or legal materials. This normative research is often referred to as literature research or document study because it focuses more research on secondary data. This secondary data relates to the analysis of civil law regarding juridical review of legal protection to copyright holders of photography. Based on the results of this study it can be concluded that the government through Article 1 paragraph 1 UUHC. 28 Years 2014 affirms the Copyright Holder is the Creator as the copyright owner, while in UUHC America 1976 Tittle 17, Article 102 which is copyright protection for original authorship includes ideas, procedures, processes, systems, methods of operation, concepts, principles or invention, regardless of the form in which it is described, described, described, or manifested. That pursuant to those articles explains the author is the holder of exclusive rights and photography is a protected work.